Iron regulated surface determinants of Staphylococcus aureus and S. lugdunensis : their roles in pathogen-host interactions - Zapotoczna, Marta Anna (Trinity College (Dublin, Ireland). School of Genetics and Microbiology, 2013)
Staphylococcus aureus is a human pathogen that causes invasive infections. The ability to internalize into and persist within host cells is thought to contribute to pathogenesis. The study described here has identified a novel role for the well characterized haemoglobin receptor of S. aureus, the iron regulated surface determinant B (IsdB). IsdBsA was shown to promote bacterial adherence to human embryonic kidney cells (293T), human cervical cancer cells (HeLa) and platelets.
Keywords: Genetics & Microbiology, Ph.D.; Ph.D. Trinity College Dublin.